Residual effect of plantaintargeted manure on substrate fertility and performance of follower maize (Zea mays) crop - Baiyeri, K.P.; Tenkouano, A.; Aba, S.C. (2009)
Fertilizer placement method plays a vital role in modulating crop response to nutrients. Previous studies found a split combination of top-dressing and base placement of poultry manure superior (on growth and dry matter yield of plantain) to either of the placement methods used singly. The present study investigated the effect of manure placement method vis-à-vis the duration of growth of a previous plantain crop on the substrate fertility (nutrient leftover) and growth of a follower maize crop. In a pot experiment, three manure application methods, consisting of top-dressing (T1), base placement (T2), or a split combination of methods T1 and T2 (T3), were tested against a no manure control (T4) on growth and dry matter yield of ‘PITA 14’ (a plantain hybrid) for a growth period of 3 or 5 months. The residual fertility of the leftover substrates was evaluated, based on growth and biomass production of two maize varieties (acid and non-acid tolerant) for 9 weeks. The acidity, organic matter and NPK contents of the substrates were determined. Data were collected on percentage seedling emergence and vigour, plant height, stem diameter, number of live leaves, leaf area, leaf area index (LAI) and dry weights of shoot and root components. The duration of growth of the previous plantain crop and the manure placement methods significantly (P < 0.05) influenced nutrient leftover and all the growth parameters of the follower maize crop. The acid tolerant maize variety generally performed better than the non-tolerant variety. Longer duration of growth of the previous plantain crop reduced residual NPK. Top dressed soil (T1) substrate previously cropped for three months supported maize plants that had the highest LAI (0.56) and total dry weight (2.39g) at 3 WAP. However, at 6 and 9 WAP, substrates with split combination of top-dressing and base placement (T3) supported the highest LAI and total dry matter yield of maize. T3 substrates also maintained the highest residual nutrients and an ideal pH (6.6) for plant growth. Irrespective of manure placement method, maize growth performances were better in substrates previously cropped for three months than those cropped for five months. Maize performance in soil amended with manure but not previously cropped (positive control) was not better than other manured substrates, particularly those cropped for 3 months. The quantity of residual K had the highest correlation coefficient with LAI and total dry weight of maize. The results implied that nutrient mining and associated soil impoverishment in plantain cultivation could be ameliorated through appropriate nutrient placement methods. A split combination of top-dressing with base placement of poultry manure in plantain fields ensures a slower but steadier availability of crop nutrients needed for better sustainability of crop yields.